Current practices in children with severe acute asthma across European PICUs: an ESPNIC survey - Boeschoten, Shelley (Eur J Pediatr, 2019)
Most pediatric asthma guidelines offer evidence-based or best practice approaches to the management of asthma exacerbations but struggle with evidence-based approaches for severe acute asthma (SAA). We aimed to investigate current practices in children with SAA admitted to European pediatric intensive care units (PICUs), in particular, adjunct therapies, use of an asthma severity score, and availability of a SAA guideline. We designed a cross-sectional electronic survey across European PICUs. Thirty-seven PICUs from 11 European countries responded. In 8 PICUs (22%), a guideline for SAA management was unavailable. Inhaled beta-agonists and anticholinergics, combined with systemic steroids and IV MgSO(4) was central in SAA treatment. Seven PICUs (30%) used a loading dose of a short-acting beta-agonist. Eighteen PICUs (49%) used an asthma severity score, with 8 different scores applied. Seventeen PICUs (46%) observed an increasing trend in SAA admissions. Conclusion: Variations in the treatment of children with SAA mainly existed in the use of adjunct therapies and asthma severity scores. Importantly, in 22% of the PICUs, a SAA guideline was unavailable. Standardizing SAA guidelines across PICUs in Europe may improve quality of care. However, the limited number of PICUs represented and the data compilation method are constraining our findings. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00431-019-03502-9) contains supplementary material, which is available to authorized users.